Resiliens mellem individ og livsform - Munk, Martin D. (Slagmark - Tidsskrift for idéhistorie, 2018)
In this paper it is demonstrated how the understanding of resilience is enhanced and shaped when using the concepts of oikos (the Greek word for household) and life-modes. Instead of applying a rather problematic welfare capitalism model, which partially provides a negative social reproduction and production, it is suggested to apply a household/family model. The household/family model outlines that positive social reproduction and production, including real and productive values, potentially creates an essential bond between viable household, family, work, socialisation, and network based communities, resulting in socially, economically, mentally, and ecologically sustainable survival of families and livelihoods over generations. Furthermore, it is stressed that serious fallacies will occur if resilience is solely understood and explained in terms of individual resources and characteristics. Nonetheless, it is recognised that non-cognitive traits such as persistence are important. Offspring is more strongly socialised and positioned in intact and viable families by transmitting and practicing a set of long-term reproduction and production strategies, which compared to upper strata are less common in the lower and middle strata. Thus, resilience is unequal.